The Competency Assessment Model for Public Transport Drivers based on the Indonesian National Qualifications Framework (KKNI) uses Analytical Hierarchy Process - Nur Kumala Dewi (Publisher Cv. Inara, 2021)
This driver behavior assessment model discusses the expertise of public transport drivers based on the national Work Qualification with graduate competency standards (SKL). Graduate competency standards have parameters, namely competence, competency elements and graduation indicators. From these three parameters, the competency unit is abbreviated as UK, the competency element is abbreviated as EK, and the graduation indicator is abbreviated as IK. Assessment of the first competency unit is upon attitudes and values, the second competency unit is upon the ability in the field of work, the third competency unit isupon the area of ??knowledge mastered and the fourth competency unit is upon the rights and responsibilities. The first competency unit has 6 competency elements and 6 graduation indicators, the second competency unit has 27 competency elements and 41 graduation indicators, the third competency unit has 6 competencies and 11 graduation indicators, the fourth competency unit has 2 competency elements and 4 graduation indicators. The first unit is abbreviated as UK1, the first competency element is abbreviated as EK1, while for the first indicator of graduation is abbreviated as IK1. The combination of UK1, EK1 and IK1 becomes UK1EK1. The combination of the first competency unit becomes the first competency element and combined to become the first graduation indicator then becomes UK1IK1, and so do the next competency unit up to the fourth competency unit. The completion stages of this discussion is carried out in four steps, namely problem identification, model design, implementation and system evaluation. The calculation process uses Analytic Hierarchy Process (AHP).